Stability augmentation for longitudinal modes of a small blended wing-body aircraft with canard as control surface / Rizal Effendy Mohd Nasir and Wahyu Kuntjoro - Mohd Nasir, Rizal Effendy; Kuntjoro, Wahyu (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
Failure to achieve satisfactory level for transient response of an aircraft in longitudinal motion - short period mode and phugoid modes - would mean poor flying and handling qualities leading to unnecessary pilot workload. This study proposes a stability augmentation system in longitudinal fly ing modes for steady and level flight at all airspeeds and altitudes within Baseline-II E-2 BWB s OFF. The main controlling component of this stability augmentation system is a set of canard. It must be able to compensate Baseline-II E-2 BWB poor transient responses 'damping ratios so that good flying quality can be achieved. Observation from the transient responses of the unaugmented system signify high-frequency short-period oscillations with almost constant low damping ratio at an altitude, and low-frequency phugoid oscillation with varying damping ratio depending on airspeed. A conclusive behaviour of natural frequencies and damping ratios against dynamic pressure leads to the understanding on how dynamic pressure influences the flying qualities. Derivation of dynamic equations in terms of dynamic pressures enables one to design and device a feedback system to compensate poor flying qualities of the original unaugmented aircraft with conclusive relationship between important parameters and dynamic pressure are put in the overall dynamic equation. Two feedback gain systems, pitch attitude and pitch rate gains are scheduled based on dynamic pressure values and are combined into the aircraft longitudinal SAS. The proposed SAS has proven to be the suitable candidate for Baseline-II E-2 BWB as it is able to ensure Level 1 flying qualities, longitudinally.